Adsorptive Removal of Cd(II) Ions from Wastewater Using Maleic Anhydride Nanocellulose - Hizkeal Tsade Kara; Sisay Tadesse Anshebo; Fedlu Kedir Sabir (Journal of Nanotechnology)
In this study, both pristine cellulose nanocrystalline (CNC) and maleic anhydride functionalized cellulose nanocrystalline (MA-CNC) were prepared from the stems of Eichhornia crassipes weed by the sulfuric acid hydrolysis method. The as-prepared adsorbents were characterized by using X-ray diffraction (XRD), Fourier-transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), energy-dispersive X-ray (EDX), and Brunauer–Emmett–Teller (BET) instruments. These materials were applied for the removal of Cd(II) ions from WW. The uptake mechanism was fixed to both Langmuir and Freundlich adsorption isotherms with a maximum Cd(II) ion uptake capability (qmax) of 75.76 and 215.52 mg g−1 by CNC and MA-CNC adsorbents, respectively. Pseudo-second-order (PSO) kinetic model was well fitted to the uptake process. The adsorbent regeneration study was done after desorption of Cd(II) ions from the adsorbent by HCl washing. Results exhibited that the adsorbent was reused for the removal of Cd(II) ions from real WW after successive 13th cycle.